Opportunities for Changes in Food Security Status at the Regency Level in Papua Island 2019-2023 - Azzahra, Dea Latifa; Emalia, Zulfa (CV. ITTC INDONESIA, 2025)
Food security is a strategic issue that reflects community welfare and regional development stability. This study aims to analyze the factors that influence the opportunity to improve food security status at the district level in Papua and West Papua Provinces during the 2019–2023 period. This study uses secondary data obtained from official agencies, such as the Central Statistics Agency and the National Food Agency. The analysis method used is binary logistic regression, with a nominal-scale dependent variable. The results of the study show that increasing rice productivity and the Human Development Index (HDI) significantly increase the opportunity for a region to achieve food security status. Conversely, the high share of community expenditure on food significantly decreases this opportunity. These findings provide important implications for the formulation of regional development policies, especially in integrating agricultural, social, and basic infrastructure sector strategies to strengthen food security in a sustainable manner.